CTGF/CCN‐2 over‐expression can directly induce features of skeletal muscle dystrophy - María Gabriela Morales; Claudio Cabello‐Verrugio; Cristian Santander; Daniel Cabrera; Roel Goldschmeding; Enrique Brandan (My University, 2011)
AbstractMuscular dystrophies are diseases characterized by muscle weakness together with cycles of degeneration and regeneration of muscle fibres, resulting in a progressive decrease of muscle mass, diminished muscle force generation and an increase in fibrosis. Fibrotic disorders are the endpoint of many chronic diseases in different tissues, where accumulation of the extracellular matrix (ECM) occurs. Connective tissue growth factor CTGF/CCN2, which is over‐expressed in muscular dystrophies, plays a major role in many progressive scarring conditions. To test the hypothesis that CTGF might not only contribute conversion of already damaged muscle into scar tissue, but that it could by itself also directly contribute to skeletal muscle deterioration, we evaluated the effect of CTGF over‐expression in tibialis anterior muscle of wild‐type mice, using an adenovirus containing the CTGF mouse sequence (Ad–mCTGF). CTGF over‐expression induced extensive skeletal muscle damage, which was followed by a massive regeneration of the damaged muscle, as evidenced by increased embryonic myosin and fibres with centrally located nuclei. It also induced strong fibrosis with increased levels of fibronectin, collagen, decorin and α‐smooth muscle actin (α‐SMA). Moreover, CTGF over‐expression caused a decrease of the specific isometric contractile force. Strikingly, when CTGF over‐expression stopped, the entire phenotype proved to be reversible, in parallel with normalization of CTGF levels. Thus, CTGF not merely acts downstream of muscle injury but also contributes directly to the deterioration of skeletal muscle phenotype and function. Moreover, normalization of expression levels led to spontaneous reversal of the CTGF‐induced phenotype and to full recovery of muscle structure. These observations underscore the importance of CTGF in the pathophysiology of muscular dystrophies and suggest that targeting CTGF might have significant potential in the development of novel therapies for Duchenne muscular dystrophy and related diseases. Copyright © 2011 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.
Keywords: connective tissue growth factor; skeletal muscular dystrophies; fibrosis; skeletal muscle damage